The effect of financial literacy, digital literacy, and entrepreneurial learning outcome on entrepreneur behavior of students at SMK Negeri 1 Surabaya - Illa Mudasih; Waspodo Tjipto Subroto; Susanti (Technium Social Sciences Journal, 2021)
This study aims to describe the research variables which include financial literacy, digital literacy, entrepreneurial learning outcomes and entrepreneur behavior and to analyze the effect of financial literacy, digital literacy, and entrepreneurial learning outcomes on student entrepreneur behavior at SMK Negeri 1 Surabaya. This research is a type of explanatory research with a quantitative approach. The population and sample in this study were students of SMK Negeri 1 Surabaya with a population of 102 students and a sample size of 81 students. The data collection technique used tests and questionnaires. The data analysis technique used multiple linear regression analysis. The results of the study of multiple linear regression data analysis show that financial literacy has a significant effect of 0.030 on the entrepreneur behavior of students at SMK Negeri 1 Surabaya and it is evident from the tcount of 2.215> t table of 1.99125. So it can be argued that an increase in financial literacy is followed by an increase in entrepreneur behavior. Digital literacy has a significant effect of 0.002 on the entrepreneur behavior of students at SMK Negeri 1 Surabaya and it is evident from the tcount of 3.259> t table of 1.99125, an increase in digital literacy is followed by an increase in entrepreneur behavior. And entrepreneurial learning outcomes have a significant effect of 0.001 on the entrepreneur behavior of students at SMK Negeri 1 Surabaya. It is proven that tcount is 3.429> 1.99125, an increase in entrepreneurial learning outcomes is followed by an increase in entrepreneur behavior. Financial literacy, digital literacy and entrepreneurial learning outcomes simultaneously on the entrepreneur behavior of students of SMK Negeri 1 Surabaya is evident from the Fcount of 13.9645> Ftable of 2.72. The number of contributions of the influence of the variables of financial literacy, digital literacy, and entrepreneurial learning outcomes on entrepreneur behavior is 32.7%, while 67.3% is influenced by other factors.